Chronic Inflammatory Polyneuropathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
Thirteen children with chronic inflammatory demyelinating polyneuropathy monitored between 1975 and 2005 are reported from Centre hospitalier universitaire Sainte-Justine, Montreal, Canada.